2015
DOI: 10.1109/tit.2015.2441693
|View full text |Cite
|
Sign up to set email alerts
|

On the Two-User MISO Broadcast Channel With Alternating CSIT: A Topological Perspective

Abstract: Abstract-In many wireless networks, link strengths are affected by many topological factors, such as different distances, shadowing, and intercell interference, thus resulting in some links being generally stronger than other links. From an information theoretic point of view, accounting for such topological aspects is still a novel approach, that has been recently fueled by strong indications that such aspects can crucially affect transceiver and feedback design, as well as the overall performance. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…where inequality (a) is obtained by using (7) and substituting (12) in (6), and the second inequality (b) is obtained by using (9), after substituting the asymptotic approximations from (10) and (11). As shown below in Lemma 2, the expression in (13) is maximized for both weak and strong interference when r = 0, and thus, we substitute r = 0 to obtain the inequality in (c).…”
Section: Proof Of Outer Boundmentioning
confidence: 99%
See 1 more Smart Citation
“…where inequality (a) is obtained by using (7) and substituting (12) in (6), and the second inequality (b) is obtained by using (9), after substituting the asymptotic approximations from (10) and (11). As shown below in Lemma 2, the expression in (13) is maximized for both weak and strong interference when r = 0, and thus, we substitute r = 0 to obtain the inequality in (c).…”
Section: Proof Of Outer Boundmentioning
confidence: 99%
“…More recently, [12] studied the GDoF region of the two-user MISO BC with fixed and alternating topologies (link strengths) under alternating CSIT, where the CSIT state of each link can be either perfect and instantaneous (P), delayed (D) or not known (N). Inner and outer bounds on the GDoF under delayed CSIT were obtained therein, which are, however, not tight, so that the characterization of the GDoF region of even a two-user MISO BC with a static topology and delayed CSIT remains an open problem.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Figure 7a illustrates the system model for state (I 1,t , I 2,t ) T = (D, N) T . When considering an entire transmission interval spanning multiple channel uses, the transmitters are interested in knowing the fraction of the transmission time (a) β I 1 ,I 2 during which the CSIT state is given by any pair (I 1 , I 2 ) T ∈ {P, D, N} × {P, D, N} [9] and (b) β A 1 ,A 2 during which the topology state is given by any pair (A 1 , A 2 ) T ∈ {γ, 1} × {γ, 1} [62,63]. Thus, effectively, β I 1 ,I 2 and β A 1 ,A 2 correspond to two-dimensional probability mass functions that depend on the pair of random variables (I 1 , I 2 ) and (A 1 , A 2 ), respectively [64].…”
Section: Alternating Csit With Fluctuating Topologymentioning
confidence: 99%
“…Furthermore, an opportunistic rate splitting scheme was proposed in [19] for an RIS-aided two-user MISO system. In particular, by utilizing the RIS to modify the channel characteristics through an alternating CSI formulation, which was inspired by the information theoretic framework presented in [20], it was shown that the achievable rate of such systems can be improved.…”
Section: Introductionmentioning
confidence: 99%